Eukaryogenesis: The Rise of an Emergent Superorganism - Bell, Philip J. L. (Frontiers in Microbiology, 2022)
Although it is widely taught that all modern life descended via modification from a last universal common ancestor (LUCA), this dominant paradigm is yet to provide a generally accepted explanation for the chasm in design between prokaryotic and eukaryotic cells. Counter to this dominant paradigm, the Viral Eukaryogenesis (VE) hypothesis proposes that the eukaryotes originated as an emergent superorganism and thus did not evolve from LUCA via descent with incremental modification. According to the VE hypothesis, the eukaryotic nucleus descends from a viral factory, the mitochondrion descends from an enslaved alpha-proteobacteria, and the cytoplasm and plasma membrane descend from an archaeal host. A virus initiated the eukaryogenesis process by colonising an archaeal host to create a virocell that had its metabolism reprogrammed to support the viral factory. Subsequently, viral processes facilitated the entry of a bacterium into the archaeal cytoplasm which was also eventually reprogrammed to support the viral factory. As the viral factory increased control of the consortium, the archaeal genome was lost, the bacterial genome was greatly reduced, and the viral factory eventually evolved into the nucleus. It is proposed that the interaction between these three simple components generated a superorganism whose emergent properties allowed the evolution of eukaryotic complexity. If the radical tenets of the VE hypothesis are ultimately accepted, current biological paradigms regarding viruses, cell theory, LUCA, and the universal Tree of Life (ToL) should be fundamentally altered or completely abandoned.